المفردات الاصطلاحية من كتاب منحة العلام في إثراء لغة الطلاب بجامعة الراية - Abdul Fatah; Mada Wijaya Kusumah (Rayah Al-Islam, 2019)
Language is the gate of knowledge, without it, the humans will not be able to communicate with other people and will not be able to exchange ideas with others, because language is a communication mechanism between them to achieve their goals. Arabic is rich in legitimate vocabulary related to religion, so there are several vocabularies or words that cannot be understood only by knowing the meaning of language, so Arabic students must know the meaning of terminology words, because the terminology words include sentences that are rarely used in conversation, so the students get difficulty in using it in daily conversation, because the terminology words are included in the intellectual sentence. The purpose of this study is to make it easier for learners of Arabic to know the terms in the book of Minhatu al 'Allam (fourth vol.) and help them choose vocabulary when speaking, writing, reading and listening. The study uses descriptive analysis methods, namely by tracing the terms in this book. This research proves the existence of the term sentence in the book of Minhatu al 'Allam (fourth vol.). The term sentence reaches 53 words. This study also formulated effective ways to enrich the language of the STIBA Ar Raayah students, namely by making a term sentence table by explaining each term etymologically and terminologically, and presenting it in the form of daily conversation and writing.